2020
DOI: 10.1044/2019_aja-19-00061
|View full text |Cite
|
Sign up to set email alerts
|

Recurrences in Sudden Sensorineural Hearing Loss: A Long-Term Observational Study

Abstract: Purpose Long-term outcomes of sudden sensorineural hearing loss (SSNHL) are poorly studied. The recurrence rate is heterogeneous, and the prognosis of relapses is uncertain. The aim of this retrospective study was to evaluate the recurrence rate of SSNHL and to analyze the correlation with clinical and audiometric characteristics. Method Seventy-three patients with idiopatic SSNHL were evaluated. Clinical and audiometric features were recorded. Seventy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Tinnitus is a phantom auditory sensation that reduces quality of life for millions worldwide (Shore et al, 2016), affecting approximately 4 to 15% of the population (Baguley et al, 2013). It has been related to listening to loud music (Axelsson and Prasher, 2000), head and neck injuries, sudden sensorineural hearing loss (Pecorari et al, 2020), ototoxic drug use (Dille et al, 2010), and other medical conditions that can affect hearing. Chronic tinnitus can trigger a range of problems, including cognitive problems, sleep disturbances (Schecklmann et al, 2015), depression (Dobie, 2003), and work disorders (Heller, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Tinnitus is a phantom auditory sensation that reduces quality of life for millions worldwide (Shore et al, 2016), affecting approximately 4 to 15% of the population (Baguley et al, 2013). It has been related to listening to loud music (Axelsson and Prasher, 2000), head and neck injuries, sudden sensorineural hearing loss (Pecorari et al, 2020), ototoxic drug use (Dille et al, 2010), and other medical conditions that can affect hearing. Chronic tinnitus can trigger a range of problems, including cognitive problems, sleep disturbances (Schecklmann et al, 2015), depression (Dobie, 2003), and work disorders (Heller, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the present study found that the mean times to recurrence were 43.2 days in patients who recovered from the recurrent episode and 44.9 days in those who did not recover. The cumulative relapse rates in studies included in the systematic review ranged from 4.9% to 47% [ 7 , 8 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of SSNHL is rare [12], unless there are underlying systemic, autoimmune or neurologic disorders [13]. Fushiki et al…”
Section: Discussionmentioning
confidence: 99%
“…The second unique feature of the case presented is the configuration of the audiogram in the initial incident affecting the lower and higher frequencies and preserving the mid ones followed by a partial recovery, whereas recurrence affected mainly the low frequencies. Recurrence of SSNHL is unusual and typical audiometric patterns are not available in relevant studies [12,23,24]. Cochlear hydrops cannot be precluded but high frequency involvement on the initial attack is atypical.…”
Section: Discussionmentioning
confidence: 99%